The boy who reversed himself - Sleator, William (New York : E.P. Dutton, 1986)
When Laura discovers that the unpopular boy living next door to her has the ability to go into the fourth dimension, she makes the dangerous decision to accompany him on his journeys there.
6.5
5-8.
Keywords: Science fiction; Science fiction